Applying diffusion of innovation theory and unified theory of acceptance and use of technology (UTAUT) on farmers’ use of communication technology - Mahamood, Ahmad Fahmi; Mohammed, Rosli; Ahmad, Mohd Khairie; Ridzuan, Ahmad Hifzurrahman; Hamzah, Mohamad Rezal; Abdullah, Shuhairimi; Shaffril, Hayrol Azril (Universiti Malaysia Perlis, 2016)
The study is focused on the use of communication technology in agricultural development.It is inevitable for the farmers to utilise the communication technology, which is a well known innovation, in order to get hold of various agricultural information that could help them to heighten the quality and quantity of agricultural products.Innovation is the implementation of ideas, products, practices, and services that adds the value to individuals (Rogers, 2003).The Malaysian farmers are merely way behind in terms of utilizing communication technology, which have prompted the researchers to look at this phenomenon in greater depth. The aim of this study is to help more farmers to use communication technology, henceforth naturally increases the number of knowledgeable and informative farmers.Based on Diffusion of Innovation Theory and Unified Theory of Acceptance and Use of Techology (UTAUT), this study observes the effectiveness of the combination of these two theories specifically on the use of communication technology among farmers. The construct of innovation characteristics includes relative advantages, compatibility, trialibility, complexity, and observability, whereas the construct of technology acceptance includes effort expectation, performance expectations, social influence, and facilitating situation. A total of 398 malaysian farmers were involved in this study as the respondents. The result shows that the use of communications technology such as interactive media and social media, can largely be utilised by the farmers, as the use and the acceptance of communication technology have increased.A linear regression test has shown the effect on the Diffusion of Innovation Theory and UTAUT is at 10.2 variance changes.Thus, the combined use of these 2 theories suits effectively to be the foundation to investigate the use of the communication technology among farmers.This model can be improved or further modified for future research to identify other factors that could play a role in the use and acceptance of innovation, especially among farmers.